COMPARATIVE STUDIES OF FELINE VIRAL RHINOTRACHEITIS VIRUS FOR ITS REPLICATION PROPERTIES IN DIFFERENT CELL CULTURES - Ye. G. Kokorina; E. I. Elizbarashvili (Ветеринария сегодня)
The results of comparative studies of feline viral rhinotracheitis virus for its culture properties in primary and continuous cell cultures of feline origin (FK, FK (subculture), CrFK, FS, CC-81, FC/Tg) are presented. It was found that viral rhinotracheitis virus replication, irrespective of the route of infection and the culture technique, was consistent and practically equal in susceptible cell cultures. The most pronounced cytopathic effect (more than 75% monolayer degeneration) was observed in all types of cell cultures in 48–72 hours of cultivation. However, the accumulation of feline viral rhinotracheitis virus Grand strain was highest when preliminary adsorption occurred within the specified period of time, monolayer cell cultures were infected with the virus at a dose of 5.5 lg TCID50/ml and roller bottle cultivated, and the рН of the medium was maintained at 7.0–7.4. Single freezing of the virus at a temperature of minus 60 degrees Celsius upon the completion of the cultivation cycle (during 60–72 hours) and its thawing were found to significantly increase the virus titre by 0.5 lg TCID50/ml.